DESAIN CONTENT MARKETING MEDIA SOSIAL GUNA MEMBANGUN BRAND AWARENESS DAYA POTENSIA INDONESIA - Adheliana, Dela; Sandy, Sandy (ADMIT: Jurnal Administrasi Terapan, 2023)
Abstract Because content marketing has become a trend and the primary foucs of many brands in increasing social media engagement, the use of visual design and copywriting techniques is an important consideration for any content marketer. As a result, the purpose of this research is to create a content marketing design for Instagram in order to raise brand awareness of Daya Potensia Indonesia (DPI). The research method used is a qualitative-decriptive method that is supported by the distribution of questionnaires to determine the impact of content design. SWOT analysis, Instagram parameter data analysis, and brand awareness level analysis are used in this research data analysis method. DPI’s content marketing management strategy was developed through eight stages, namely goal setting, target market mapping, content initiation and planning, content creation, content distribution, content strengthening, content evaluation, and content improvement. The content marketing strategy that prioritizes content creation through visual design and copywriting can increase engagement by 363%, account reach by 539%, and follow-up with a significant increase in followers of 282. According to the finding of the brand awareness analysis, 69% of respondents stated that they were familiar with the DPI brand. Thus, it is known the Daya Potensia Indonesia brand has succeeded in occupying the brand recognition position, so that 69 respondents in this research still need to be reminded of the DPI brand’s existence through massive promotions on Instagram or other media.